Retention of educators through the lens of Bronfenbrenner’s theory - Young, Krystal Ann (My University, 2025)
This qualitative study explored the retention of teachers through the lens of Bronfenbrenner's ecological systems theory. The research aimed to understand the multifaceted factors influencing teacher retention by examining the interplay between individual, interpersonal, organizational, and societal levels within the teaching environment. Twelve teachers, six novice and six veteran, were interviewed to gather in-depth insights into their professional experiences and the various ecological systems that contributed to their decisions to stay in the teaching profession. Bronfenbrenner's theory provided a comprehensive framework for analyzing the dynamic interactions between teachers and their environments. The study employed interviews as the primary data collection method, allowing participants to share their narratives and perspectives. Themes emerging from the interviews were analyzed to identify patterns and connections within the microsystem (individual factors), mesosystem (interpersonal relationships), exosystem (organizational influences), macrosystem (societal factors), and the chronosystem (changes over time) that impacted teacher retention. The research concluded that the mesosystem, which encompasses relationships within the school system, had the most significant impact on teachers remaining in their careers. This finding was exhibited by both the novice and veteran groups, highlighting the critical role that interpersonal relationships play in teacher retention. Supportive relationships with colleagues, administrators, and the broader school community were consistently identified as key factors influencing teachers' decisions to stay in the profession. By utilizing Bronfenbrenner's theoretical framework, this research contributed to the existing knowledge on teacher retention by offering a holistic understanding of the interconnected factors influencing teachers' decisions to remain in the profession. The findings underscored the importance of fostering positive and supportive relationships within the school environment to enhance teacher retention across different career stages.
Keywords: Retention of educators; Bronfenbrenner’s theory; Retention